Attitudes Toward Opioid Use for Chronic Pain: A Canadian Physician Survey - Patricia K Morley-Forster; Alexander J Clark; Mark Speechley; Dwight E Moulin (Pain Research and Management)
OBJECTIVES: To measure chronic pain patient volumes seen in primary care practice; to determine what medications physicians choose for the treatment of moderate to severe chronic pain; to identify barriers to the use of opioids in the treatment of chronic pain; and to assess physicians' attitudes toward the current management of chronic pain in Canada.